Giant endometrial polyp: An enigma in a postmenopausal woman - Sonam Sharma (Wolters Kluwer Medknow Publications, 2018)
Giant polyp is an unusual female genital tract pathology, commonly arising from the cervix than the endometrium. It is a great masquerader of cervical or endometrial malignancy and can lead to a diagnostic dilemma and unnecessary aggressive interventions. Experience in one such case of an extremely rare protruding giant endometrial polyp in a 58-year-old postmenopausal female is being described herewith so as to create awareness among the dealing clinicians. The approach to such a case, differential diagnosis, and review of the literature is also presented.